Berinteraksi Dengan Al-Qur’an: Studi Atas Pemikiran Wasfi Asyur - Fratama, Risal; Husna, Jannatul; Waharjani, Waharjani (State Islamic University of Datokarama Palu, 2023)
The facts explain that humans seem to avoid and do not approach the Qur'an. This means that humans have not been able to interact with the Qur'an. Wasfi Ashur, his thoughts related to interacting with the Qur'an. The method in this research is a Library. This study aims to examine how to interact with the Qur’an based on Wasfi Ashur's thoughts. The results of this study indicate that there are 8 principles of how to interact with the Qur’an based on Wasfi Ashur's thinking. They are (1) Knowing the value of the Qur’an. (2) Knowing the purpose of the Qur'an. (3) Know Allah as God Almighty and be close to Him. (4) Read the Qur'an correctly. (5) Memorize the Qur'an. (6) Understand the contents of the Qur'an. (7) Action and practice the contents of the Qur'an. (8) Spread the contents of the Qur'an.